Analysis of the Elimination of Fixed Assets at the Upt Office of Labor Supervision Region I of North Sumatra Province - Icha Puji Usti; Rahmat Daim Harahap (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this study was to find out about the accounting treatment of disposal and disposal of assets carried out at the Office of Upt Labor Supervision Region I of North Sumatra Province and to find out whether the agreement between the accounting treatment of write-off and disposal of state-owned assets was in sync with the Statement of Financial Accounting Standards or not. The object of this research is the Upt Office of Labor Supervision Region I, North Sumatra Province. This research information uses qualitative object information techniques derived from primary data and secondary data. The results of this study indicate that in carrying out the process of terminating regional fixed assets which has been carried out by the Regional I Employment Supervision Upt Office of North Sumatra Province, it has not been in accordance with the Statement of Financial Accounting Standards in terms of the disposal of the company's fixed assets without recording losses, this is due to the disposal of assets. at the Regional I Labor Supervision Upt Office not yet in accordance with PSAK 16 concerning the write-off of fixed assets.